TEACHING ENGLISH TO JOURNALISM STUDENTS BASED ON THE SPECIFICS OF JOURNALISTIC GENRES (SCIENCE TIME JOURNAL, 2025)
this article explores methods of teaching English to journalism students by integrating the linguistic, stylistic, and structural features of journalistic genres. It examines how genre-specific tasks enhance language competence, critical thinking, and professional writing skills. The study offers pedagogical strategies aligning language instruction with the practical demands of journalistic practice in multimedia and cross-cultural communication contexts.